Islamic finance in Morocco: What answers to financing problems of SMEs? State of play and perspectives: Finance participative au Maroc : Quelles réponses aux problèmes de financement des PME ? État des lieux et perspectives - HAISSOUNE, Mohamed; IZIKI , Ilias (African Scientific Journal, 2021)
SMEs are the core of the Moroccan economy, they represent a large part of the country’s economic fabric and considerably participate in employment, value creation and economic growth. However, SMEs are exposed tovarious obstacles that they need to deal with, especially in terms of financing. Islamic finance isrecently established in Morocco. It improves the financial market and offers new financial instruments that are designed based on commercial and partnership interactions with the company. Therefore, Islamic finance brings back hope to the SMEs that expect to find in this new form of financing ways to address the problems they face. This article’saimis not only to provide aclear understanding of the Moroccan Islamic finance model, but also, to high light the difficulties encountered by Moroccan SMEs in terms of conventional financing and, to capture what SMEs’s managers think about the Islamic financing. Résumé Les PME sont le noyau de l’économie marocaine. Elles présentent une grande part du tissu économique marocain et participent fortement à l’emploi, à la création de la valeur et à la croissance économique. Cependant, Les PME doivent faire face à différents obstacles notamment en matière de financement. Récemment implantée au Maroc, la finance participative vient améliorer le marché financier et proposer des nouveaux instruments financiers basés sur une relation commerciale et un partenariat avec l’entreprise. Par conséquent, un grand espoir est porté sur ce nouveau mode financement pour remédier aux problèmes que rencontrent les PME. L’objet de cet article est d’abord de comprendre le modèle marocain de la finance participative, puis, de constater les difficultés rencontrées par les PME marocaines en matière de financement conventionnel et, enfin, appréhender la perception des dirigeants des PME envers le financement participatif. Mots-clés : Financement de l’économie – Finance islamique - Finance participative – PME